Increasing The Quality Of Dry Seaweeds By Drum Washing Machine - Muhamad Firdaus (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2015)
AbstractJabon area, Sidoarjo district is one of shoreline area that it have about 40 percentage of this is ponds. These used farming of agarophyte seaweeds, i.e. alga producing agar-agar, such as Gracilaria sp. Postharvest activity of this by farmer comprise of plucking, bringing, drying, and packaging produce quality of dry seaweeds lower than Indonesia National Standard and cause cheap price. The purpose of this study was to obtain increasing quality of dry agarophyte seaweeds by drum type of washing machine. The method of this activity was Participatory Rural Appraisal involving enlightenment, demonstration, and partnership in using of drum washing machine to group of farmer and seaweed cultivator on Tegalsari village, Jabon area, Sidoarjo district. The result showed that partner followed enthusiastically the enlightenment, demonstration, and partnership. The quality of dry seaweeds that washed by drum machine was rise and included in product criteria of Indonesia National Standard. The yield of dry seaweeds increased to 17.5% and the gel strength of agar-agar was higher six times and also the selling price expanded to 42% or Rp 2,500.- each kilograms. The conclusion is using drum washing machine able to increase the quality and selling price of dry seaweeds and move the increasing of prosperity of seaweed farmer and dry seaweeds cultivators.Keywords: drum washing machine, Gracilariasp, postharvest, quality, selling price.